An uncoupled thermoelasticity problem for a semi-infinite layer with regard to its proper weight - A. Fesenko; N. Vaysfeld (Fracture and Structural Integrity)
The exact solution of the uncoupled thermoelasticity problem for a semi-infinite elastic layer with regard to its proper weight was constructed. The originality of the proposed paper is based on reducing Lame equations to two jointly and one separately, solvable equations. It allows the application of integral transformations directly to the transformed equations of equilibrium and makes it possible to reduce the initial problem to a one-dimensional vector boundary problem. A special technique is given to calculate multiple integrals containing oscillating functions that appear during the inversion of the transforms. The character of the temperature and proper weight influence on the value of normal stress on the lateral face of the semi-infinite layer, the zone of tensile stress depending on the shapes of the distributed load section and the temperature and Poisson's ratio is established. The parameters of dimensionless mechanical load and temperature, when the separation of the side wall of the semi-infinite layer can be eliminated, were established. A study of the influence of the layer쒒s proper weight on the stress emerging on the layers edge is conducted. The constructed exact solution can be used as a model for solving a similar class of problems by numerical methods.